Faktor-Faktor yang Memengaruhi Nilai Perusahaan dengan Profitabilitas sebagai Variabel Mediasi pada Sektor Pertambangan di BEI Tahun 2015-2018 - Emi Mei Astutik (Jurnal Ilmu Manajemen, 2021)
The purpose of this study is to determine the effect of corporate social responsibility, dividend policy, company age, independent board of commissioners, and managerial ownership with profitability as a mediating variable. The population used is mining sector companies listed on the Indonesia Stock Exchange (BEI) in 2015-2018. By using purposive sampling, the sample is ten companies. This study using path analysis and processed with IBM SPSS 25. This study's results are only corporate social responsibility, dividend policy, and profitability that affect firm value.Meanwhile, variable company age, independent board of commissioners, and managerial ownership do not affect firm value. Investors are not interested in old companies because they cannot adapt to existing developments. Investors are also not interested in investing in companies that have agency problems. The variables that influence profitability are corporate social responsibility and independent board of commissioners. Meanwhile, dividend policy, company age, and managerial ownership cannot affect profitability. There are characteristics of some investors who do not like the distribution of dividends. Investors prefer newly established companies because they are more innovative in their business. Agency problems are also a factor that hinders investors from investing in companies. This study shows that profitability cannot be a mediating variable in this study because high profitability cannot determine high firm value.